The Effectiveness of Solution-Focused Brief Group Counseling to Increase the Optimism of Students with Academic Stress - Pujowati, Menur; Eddy Wibowo, Mungin; Mulawarman, Mulawarman (Jurnal Bimbingan Konseling, 2022)
High School students often experience high academic stress, even they are expected to achieve high academic achievement. In this case optimism holds an important role because students who have high optimism are believed to manage academic stress. Due to this background, the present study attempted to analyze the effectiveness of solution-focused brief group counseling to increase the optimism of Public Senior High School or SMA Negeri 5 Semarang students. It used pretest-posttest control group design and Life Orientation Test-Revised (LOT-R) scale to collect the data which later were analyzed using mixed ANOVA. Findings indicated that the solution-focused brief counseling has been effective to increase the optimism of students with academic stress. Thus, counselors are required to master this type of counseling to foster students’ optimism and reduce academic stress.